2013
DOI: 10.1002/14651858.cd006132.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for improving adherence to ocular hypotensive therapy

Abstract: Background Poor adherence to therapy is a significant healthcare issue, particularly in patients with chronic disease such as open-angle glaucoma. Treatment failure may necessitate unwarranted changes of medications, increased healthcare expenditure and risk to the patient if surgical intervention is required. Simplifying eye drop regimes, providing adequate information, teaching drop instillation technique and ongoing support according to the patient need may have a positive effect on improving adherence. Obj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
64
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(69 citation statements)
references
References 93 publications
0
64
1
4
Order By: Relevance
“…In another report, physical difficulty with eyedrop instillation was one of the most common barriers to success in the 27% of glaucoma subjects who self-reported poor medication adherence [34]. We speculate that a microdosing system with better accuracy and future science group www.futuremedicine.com convenience than eyedropper delivery might improve ocular self-administration consistency, and adherence to medication dosing schedules [35]. This study demonstrated different bioactivity and pharmacodynamics of ocular drugs that are delivered by microdosing versus conventional eyedropper overdosing.…”
Section: Discussionmentioning
confidence: 91%
“…In another report, physical difficulty with eyedrop instillation was one of the most common barriers to success in the 27% of glaucoma subjects who self-reported poor medication adherence [34]. We speculate that a microdosing system with better accuracy and future science group www.futuremedicine.com convenience than eyedropper delivery might improve ocular self-administration consistency, and adherence to medication dosing schedules [35]. This study demonstrated different bioactivity and pharmacodynamics of ocular drugs that are delivered by microdosing versus conventional eyedropper overdosing.…”
Section: Discussionmentioning
confidence: 91%
“…Patient education groups and individualised educational interventions in a face-to-face setting or over the telephone have been shown to improve patient understanding of the condition and medication adherence. 24 A Cochrane review by Waterman et al 25 showed that there was some evidence that patient education combined with personalised interventions improved adherence and simplified drug regimes could be of benefit, however, there was insufficient evidence to recommend a specific intervention. Limitations to our study consists of not including the length of time patients had been on glaucoma medication to ascertain if there was any correlations between the length of time and adherence, as shown in a previous study by Vanelli et al 26 Our study demonstrates that younger patients tended to have the worse adherence of all age groups; it is imperative that this group of patients are targeted for educational interventions as it is important they understand the importance of regular use of medications to prevent visual loss in their expected lifespan.…”
Section: Discussionmentioning
confidence: 99%
“…Evaluations of the intervention strategies suggest that multi-faceted, complex interventions are required to confer most benefit. 45,46 The one study to explore this arena in relation to primary eye care focused on an education campaign related to glaucoma as a means of improving attendance. The findings showed that whilst knowledge and awareness was increased, health-seeking behaviour was unchanged.…”
Section: Discussionmentioning
confidence: 99%